The Menotoring of Integrated Science Olympiad to Improve Student Achievement at Madrasah Aliyah Negeri 3 Jombang - Iis Makhisoh; Abd Rouf Hasbullah; Mas'ud (LP3M STAI At-Tahdzib Jombang, 2025)
Science Olympiad activities are a routine agenda organized by various educational institutions, including the Ministry of Religion, which organizes Science Olympiads as part of the Madrasah Science Competition. The policy of adding integrated Arabic, Islamic Education and English is a challenge in itself in this competition. Madrasah Aliyah Negeri 3 Jombang is a school that actively participates in the Science Olympiad competition considering that the quality and achievements of non-academic activities in educational institutions are currently one of the special assessments of the relevant community includes the quality of education. The aim of this Olympic mentoring program is to provide provisions to improve students’ competence in participating in the Olympics. Mentoring activities carried out using the PAR (Participatory Action Research) method. The results of this mentoring include several aspects, academically, namely increasing understanding of material, mastery of competition techniques and strategies, increasing academic achievement, while non-academic results include: Increasing interest in Arabic, Improved soft skills, time management abilities and increased collaboration between teachers and students. With these results, the mentoring program not only provides short-term benefits in the form of achievements, but also long-term positive impacts for students, madrasas and society.